Hakikat Pendidikan Terpadu: Studi Kasus Filosofi dan Praktik di SMPIT Luqman Hakim - Bunga Salwa; Mohammad Syaifuddin; Afif Sulton; Dewi Istiqomah; Dewi Aliya (Yayasan Literasi Sains Indonesia, 2025)
Boarding school-based integrated education has developed into a leading model in Indonesia's modern Islamic education system, which aims to holistically integrate knowledge, faith, and manners. This qualitative research using a case study approach aims to examine the implementation of this model at SMP IT Luqman Hakim. Data were collected through in-depth interviews with stakeholders, participant observation, and curriculum document analysis. The findings reveal that this model is based on the philosophy of forming perfect human beings who integrate mastery of science and technology and faith and morals in a balanced manner. Its implementation is reflected in: (1) an integrated curriculum that combines science with the values of the Qur'an, (2) a 24-hour boarding school system that functions as a character laboratory through the habit of worship, instilling discipline, and the continuous internalisation of Islamic manners. This study concludes that the effectiveness of boarding school-based integrated education lies in the complete synergy between a strong philosophical foundation and structured and consistent practice in a controlled educational environment.